Pengembangan Poster sebagai Media Nudging untuk Mengurangi Sisa Makanan pada Remaja di Sekolah Asrama: Development of Posters as Nudging Media for Reducing Food Waste among Teenagers in Boarding Schools - Yunianto, Andi Eka; Riyadi, Hadi; Khomsan, Ali; Baliwati, Yayuk Farida (Universitas Airlangga, 2026)
Background: Young people, especially at boarding schools, generate a large amount of food waste that may be addressed through targeted and persuasive education strategies based on context. Objectives: This study aimed to develop and evaluate nudging posters to reduce food waste behavior among adolescents. Methods: A descriptive design was used to assess the validity and reliability of four posters. Three expert panelists provided feedback to the researchers to determine the validity of the posters' content. To assess poster reliability, 60 adolescents rated the posters using a Likert scale. Data were analyzed in Excel for Aiken's V analysis and in SPSS version 25 for Spearman’s correlation and Cronbach's alpha (CCA). Results: According to the validity test, Posters 2 and 4 had the highest Aiken’s V value (0.889) for color harmony, layout, and content flow. The most valid components were the contextually appropriate and scientifically accurate content. The least valid components were the completeness of content and how well the message was emphasized (Aiken’s V=0.444 to 0.666). Language was generally the weakest component, but its validity improved when using a style that matched adolescent characteristics. Reliability analysis confirmed that the evaluation instruments were valid and reliable. Posters 1, 2, and 4 showed significant item correlations (p-value<0.05) with Cronbach’s Alpha of 0.983, indicating excellent internal consistency. Poster 3 contained one invalid item, though this did not affect overall reliability. Conclusions: The study concluded that the developed posters are valid and reliable as a form of nudging media. They demonstrate potential as effective educational tools to influence teenagers’ behavior and reduce food waste in boarding school settings.